StRAB4 gene is required for filamentous growth, conidial development, and pathogenicity in Setosphaeria turcica - Li, Pan; Zhu, Hang; Wang, Chengze; Zeng, Fanli; Jia, Jingzhe; Feng, Shang; Han, Xinpeng; Shen, Shen; Wang, Yanhui; Hao, Zhimin; Dong, Jingao (Frontiers in Microbiology, 2024)
Setosphaeria turcica, the fungal pathogen responsible for northern corn leaf blight in maize, forms specialized infectious structures called appressoria that are critical for fungal penetration of maize epidermal cells. The Rab family of proteins play a crucial role in the growth, development, and pathogenesis of many eukaryotic species. Rab4, in particular, is a key regulator of endocytosis and vesicle trafficking, essential for filamentous growth and successful infection by other fungal pathogens. In this study, we silenced StRAB4 in S. turcica to gain a better understanding the function of Rab4 in this plant pathogen. Phenotypically, the mutants exhibited a reduced growth rate, a significant decline in conidia production, and an abnormal conidial morphology. These phenotypes indicate that StRab4 plays an instrumental role in regulating mycelial growth and conidial development in S. turcica. Further investigations revealed that StRab4 is a positive regulator of cell wall integrity and melanin secretion. Functional enrichment analysis of differentially expressed genes highlighted primary enrichments in peroxisome pathways, oxidoreductase and catalytic activities, membrane components, and cell wall organization processes. Collectively, our findings emphasize the significant role of StRab4 in S. turcica infection and pathogenicity in maize and provide valuable insights into fungal behavior and disease mechanisms.